1999
DOI: 10.1007/s002130051054
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex is involved in the discriminative stimulus effects of nicotine in rats

Abstract: Together with our previous study indicating that the nucleus accumbens and the ventral tegmental area are partially involved in the DS effects of nicotine, the present study suggests that mPFC is primarily involved in the DS effects of nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Mecamylamine was used to probe for activity at central nicotinic acetylcholine receptors. Not surprisingly, mecamylamine blocked the discriminative stimulus effects of nicotine in the nicotine-trained rats, in agreement with earlier findings (Miyata et al, 1999;Rosecrans, 1989;Stolerman, 1988). Mecamylamine produced a small attenuation of the discriminative stimulus effects of methamphetamine in the methamphetamine-trained rats, but produced no effect on methamphetamine cross-substitution in the nicotine-trained rats.…”
Section: Mechanismssupporting
confidence: 91%
See 1 more Smart Citation
“…Mecamylamine was used to probe for activity at central nicotinic acetylcholine receptors. Not surprisingly, mecamylamine blocked the discriminative stimulus effects of nicotine in the nicotine-trained rats, in agreement with earlier findings (Miyata et al, 1999;Rosecrans, 1989;Stolerman, 1988). Mecamylamine produced a small attenuation of the discriminative stimulus effects of methamphetamine in the methamphetamine-trained rats, but produced no effect on methamphetamine cross-substitution in the nicotine-trained rats.…”
Section: Mechanismssupporting
confidence: 91%
“…The discriminative stimulus effects of nicotine are primarily mediated by central nicotinic receptors, such that agonists at these receptors substitute in nicotine-trained rats, and mecamylamine blocks the discriminative stimulus effects of nicotine (Miyata et al, 1999;Rosecrans, 1989;Stolerman, 1988). Other receptors also contribute to the stimulus effects of nicotine, dopamine receptors producing the largest effect.…”
Section: Mechanism Of the Discriminative Stimulus Effects Of Nicotinementioning
confidence: 99%
“…This specificity allows researchers to explore and categorize the pharmacological properties of psychoactive compounds. For example, microinjections of nicotine into the medial prefrontal cortex and dorsal hippocampus evoke nicotineappropriate responding in rats trained to discriminate nicotine from saline via subcutaneous injections (Miyata et al, 1999;Shoaib and Stolerman, 1996). In contrast, microinjections of nicotine into the nucleus accumbens or the medial habenular nucleus did not result in nicotineappropriate responding.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have determined that nicotine can alter glutamate release in several different areas of the brain, including the ventral tegmental area (Schilstrom et al, 1998(Schilstrom et al, , 2000Fu et al, 2000;Mansvelder and McGehee, 2000) the nucleus accumbens (Fu et al, 2000;Reid et al, 2000) the pre-frontal cortex (Toth et al, 1993;Vidal, 1994;Gioanni et al, 1999;) and the hippocampus (Gray et al, 1996;Radcliffe et al, 1999). These are areas thought to be involved in mediating the subjective (Rosecrans and Meltzer, 1981;Shoaib and Stolerman, 1992;Miyata et al, 1999) rewarding (Corrigall et al, 1994;Stolerman, 1996;Schroeder et al, 2001) and cognitive actions of nicotine (Stolerman, 1996;Levin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have determined that nicotine can alter glutamate release in several different areas of the brain, including the ventral tegmental area (Schilstrom et al, 1998(Schilstrom et al, , 2000Fu et al, 2000;Mansvelder and McGehee, 2000) the nucleus accumbens (Fu et al, 2000;Reid et al, 2000) the pre-frontal cortex (Toth et al, 1993;Vidal, 1994;Gioanni et al, 1999;) and the hippocampus (Gray et al, 1996;Radcliffe et al, 1999). These are areas thought to be involved in mediating the subjective (Rosecrans and Meltzer, 1981;Shoaib and Stolerman, 1992;Miyata et al, 1999) rewarding (Corrigall et al, 1994;Stolerman, 1996;Schroeder et al, 2001) and cognitive actions of nicotine (Stolerman, 1996;Levin et al, 1999).There is also growing evidence from behavioral models to indicate a role for glutamate in neurobiological mechanisms underlying the actions of nicotine. Investigators carrying out studies in rodents have reported that antagonists acting at N-methyl-D-aspartate (NMDA)-receptor sites can attenuate nicotine self-administration and the nicotine discriminative stimulus (Glick et al, 2001;Blokhina et al, 2005;Zakharova et al, 2005; but see also Wright et al, 2006) and the metabotropic GluR5 antagonist 2-methyl-6-(phenylethynyl)-pyridine (MPEP), has also been reported to be effective (Paterson et al, 2003;Paterson and Markou, 2005;Zakharova et al, 2005).…”
mentioning
confidence: 99%